Perceptions of teacher-student relationships predict reductions in adolescent distress via increased trait mindfulness - Mills-Webb, Kathryn; Hennessey, Alexandra (Frontiers in Education, 2025)
Equipping adolescents with the skills to reduce distress is a priority in education, because distress is common during this period and often a precursor to serious emotional disorders. Fostering trait mindfulness, which is associated with lower levels of perceived distress, could be an effective way to reduce distress, but little is known about how to maximise trait mindfulness, or the underlying mechanisms by which these abilities help buffer distress. This study aimed to examine the associations between teacher-student relationships and adolescents’ levels of trait mindfulness and perceived distress. We hypothesised that teacher-student relationships and trait mindfulness would directly predict reductions in perceived distress, and that trait mindfulness would partially mediate the relationship between teacher-student relationships and perceived distress. A quantitative, cross-sectional design was used to test these hypotheses. Participants were 124 UK secondary school students aged between 13 and 15 years old. They completed measures including the Five Facet Mindfulness Questionnaire, the distress subscale of the Perceived Stress Scale 10, and the Teacher-Student Relationship subscale of the Student Engagement Instrument. We found that positive teacher-student relationships significantly predicted higher levels of trait mindfulness and lower levels of perceived distress. Trait mindfulness fully mediated the relationship between teacher-student relationships and perceived distress. The findings indicate that by nurturing positive relationships between staff and students, schools can foster students’ trait mindfulness skills, in turn helping reduce perceived distress.